CD248/endosialin critically regulates hepatic stellate cell proliferation during chronic liver injury via a PDGF-regulated mechanism. Issue 7 (15th June 2015) - Wilhelm, Annika; Aldridge, Victoria; Haldar, Debashis; Naylor, Amy J; Weston, Christopher J; Hedegaard, Ditte; Garg, Abhilok; Fear, Janine; Reynolds, Gary M; Croft, Adam P; Henderson, Neil C; Buckley, Christopher D; et al.
Abstract : Introduction: CD248 (endosialin) is a stromal cell marker expressed on fibroblasts and pericytes. During liver injury, myofibroblasts are the main source of fibrotic matrix. Objective: To determine the role of CD248 in the development of liver fibrosis in the rodent and human setting. Design: CD248 expression was studied by immunostaining and quantitative PCR in both normal and diseased human and murine liver tissue and isolated hepatic stellate cells (HSCs). Hepatic fibrosis was induced in CD248 −/− and wild-type controls with carbon tetrachloride (CCl4 ) treatment. Results: Expression of CD248 was seen in normal liver of humans and mice but was significantly increased in liver injury using both immunostaining and gene expression assays. CD248 was co-expressed with a range of fibroblast/HSC markers including desmin, vimentin and α-smooth muscle actin (α-SMA) in murine and human liver sections. CD248 expression was restricted to isolated primary murine and human HSC. Collagen deposition and α-SMA expression, but not inflammation and neoangiogenesis, was reduced in CD248 −/− mice compared with wild-type mice after CCl4 treatment. Isolated HSC from wild-type and CD248 −/− mice expressed platelet-derived growth factor receptor α (PDGFR-α) and PDGFR-β at similar levels. As expected, PDGF-BB stimulation induced proliferation of wild-type HSC, whereas CD248 −/− HSC did not demonstrate a proliferative response to PDGF-BB. Abrogated PDGF signalling in CD248 −/− HSC was confirmed by significantly reduced c-fos expression in CD248 −/− HSC compared with wild-type HSC. Conclusions: Our data show that deletion of CD248 reduces susceptibility to liver fibrosis via an effect on PDGF signalling, making it an attractive clinical target for the treatment of liver injury.